No Malay tsunami in GE14 - Daily Express, (KK) (Daily Express (KK), 2017)
KUALA LUMPUR: There won't be a 'Malay tsunami' in the upcoming general election, in terms of the community's support for the Opposition, an analyst from a local university has predicted.